Outcome of Corrective Dome Osteotomy for Cubitus Varus Deformity - Ranjib Kumar Jha; Santosh Thapa; Dhiraj Singh (Journal of Nobel Medical College, 2019)
Background: The cubitus varus deformity is one of the most common late complications of fracture supracondylar area of humerus in children. Various corrective osteotomies are used of which lateral closed wedge osteotomy is commonly done which has its own disadvantages like lateral condylar prominence, difficulty in achieving correction and limitation of movement. Dome osteotomy is a versatile technique to achieve correction of deformity in all planes and to overcome these above complications. The aim of this study was to evaluate the results of dome osteotomy for correction of post-traumatic cubitus varus deformity of elbow in children.